A polymorphic CD4 epitope related to increased susceptibility to Babesia bovis in Canchim calves - Okino, Cintia Hiromi; Bassetto, Cesar Cristiano [UNESP]; Giglioti, Rodrigo; Silva, Pamella Cristini; Tonelli, Maria Fernanda; Marcondes, Cintia Righetti; Oliveira, Henrique Nunes de [UNESP]; Sena Oliveira, Marcia Cristina de (Elsevier B.V., 2020)
Different allelic forms of bovine CD4 were previously described in cattle and were also observed in Canchim calves examined in the present experiment. However, the functional relevance of these different CD4 phenotypes has not yet been investigated. CD4 + T helper cells are known to play a central role in immune control against Babesia bovis infection. Thus, our study aimed to compare the profiles of immune cells, specific antibody titers and blood infection levels measured by qPCR (quantitative polymerase chain reaction) in calves naturally infected with B. bovis, phenotyped as CD4(absence of anti-CD4 staining), CD4 + (intermediate staining) or CD4 ++ (high staining). The CD4 mRNA precursor was also measured in these animals. Calves with the CD4phenotype showed higher amounts of B. bovis DNA in blood samples, compared to the other CD4 phenotypes. It was also observed that these calves with higher levels of infection had lower amounts of natural killer cells and higher expression of the CD4 gene, which can be interpreted as a compensation for the failure of the altered CD4 receptor to recognize relevant B. bovis epitopes.
Keywords: polymorphism; Calves; Resistance; Allele; Immunophenotyping; T helper cells